Calorie Restriction-Induced Increase in Skeletal Muscle Insulin Sensitivity Is Not Prevented by Overexpression of the p55α Subunit of Phosphoinositide 3-Kinase - Martins, Vitor F.; Tahvilian, Shahriar; Kang, Ji H.; Svensson, Kristoffer; Hetrick, Byron; Chick, Wallace S.; Schenk, Simon; McCurdy, Carrie E. (Frontiers in Physiology, 2018)
Introduction: The Phosphoinositide 3-kinase (PI3K) signaling pathway plays an important role in skeletal muscle insulin-stimulated glucose uptake. While whole-body and tissue specific knockout (KO) of individual or combinations of the regulatory subunits of PI3K (p85α, p55α and p50α or p85β); increase insulin sensitivity, no study has examined whether increasing the expression of the individual regulatory subunits would inhibit insulin action in vivo. Therefore, the objective of this study was to determine whether skeletal muscle-specific overexpression of the p55α regulatory subunit of PI3K impairs skeletal muscle insulin sensitivity, or prevents its enhancement by caloric restriction. Methods: We developed a novel “floxed” mouse that, through the Cre-LoxP approach, allows for tamoxifen (TMX)-inducible and skeletal muscle-specific overexpression of the p55α subunit of PI3K (referred to as, ‘p55α-mOX’). Beginning at 10 weeks of age, p55α-mOX mice and their floxed littermates (referred to as wildtype [WT]) either continued with free access to food (ad libitum; AL), or were switched to a calorie restricted diet (CR; 60% of AL intake) for 20 days. We measured body composition, whole-body energy expenditure, oral glucose tolerance and ex vivo skeletal muscle insulin sensitivity in isolated soleus and extensor digitorum longus muscles using the 2-deoxy-glucose (2DOG) uptake method. Results: p55α mRNA and protein expression was increased ~2 fold in muscle from p55α-mOX versus WT mice. There were no differences in energy expenditure, total activity, or food intake of AL-fed mice between genotypes. Body weight, fat and lean mass, tissue weights, and fasting glucose and insulin were comparable between p55α-mOX and WT mice on AL, and were decreased equally by CR. Interestingly, overexpression of p55α did not impair oral glucose tolerance or skeletal muscle insulin signaling or sensitivity, nor did it impact the ability of CR to enhance these parameters. Conclusions: Skeletal muscle-specific overexpression of p55α does not impact skeletal muscle insulin action, suggesting that p85α and/or p50α may be more important regulators of skeletal muscle insulin signaling and sensitivity.